Ewing sarcoma in an infant and review of the literature - Bedük Esen, Çağlayan Selenge; Gültekin, Melis; Aydın, G. Burça; Akyüz, Canan; Oğuz, Kader Karlı; Orhan, Diclehan; Cengiz, Mustafa; Gürkaynak, Murat; Yıldız, Ferah (The Turkish Journal of Pediatrics, 2019)
Ewing sarcoma (ES) is a rare tumor in infants and prognosis is controversial. There are no standard recommendations for treatment in such very young patients. Generally, radiotherapy (RT) is not a part of treatment in infants due to the risk of severe late side effects. In this case report, we report a 7-month-old boy with diagnosis of left mastoid bone ES with lung metastases at diagnosis, showing a rapidly fatal outcome despite aggressive systemic chemotherapy and RT without surgery.